Відмовостійка маршрутизація з підтримкой балансування навантаження - Алексин, В. В. (ХНУРЕ, 2019)
The principle of fault-tolerant routing with load balancing support has been considered and improved. The peculiarity of such networks is that routing protocols with increased levels of fail-safe solutions are used. As shown in practice, this technology is especially needed to maintain multiserviceability. And the use of special protocols can increase the availability of routers performing the role of the gateway by order.